Role of proline isomerization in folding of ribonuclease A at low temperatures - Cook, Kem H. (1979)
In unfolded RNase A there is an interconversion between slow-folding and fast-folding forms (U(S) ⇌ U(F)) that is known to show properties characteristic of proline isomerization in model peptides. Here, we accept the evidence that U(S) molecules contain nonnative proline isomers and we ask about the isomerization of these proline residues during folding. The U(S) ⇌ U(F) reaction in unfolded RNase A is used both to provide data on the kinetics of proline isomerization in the unfolded protein and as the basis of an assay for measuring proline isomerization during folding. The tyrosine-detected folding kinetics at low temperatures have been compared to those of proline isomerization in unfolded RNase A. The comparison is based on the recent observation that the U(S) ⇌ U(F) kinetics are independent of guanidinium chloride concentration, so that they can be extrapolated to low guanidinium chloride concentrations, at which folding takes place. At 0°C the tyrosine-detected folding reaction is 100-fold faster than the conversion of U(S) to U(F) in unfolded RNase A. Consequently, the folding reaction is not rate-limited by proline isomerization as it occurs in unfolded RNase A. An assay is given for proline isomerization during folding. The principle is that native RNase A yields U(F) on unfolding, whereas protein molecules that still contain nonnative proline isomers yield U(S). Unfolding takes place at 0°C, at which proline isomerization is slow compared to unfolding. This assay yields two important results: (i) The kinetics of proline isomerization during folding are substantially faster than in unfolded RNase A—e.g., 40-fold at 0°C. The mechanism of the rate enhancement is unknown. (ii) At low temperatures (0-10°C), and also in the presence of (NH(4))(2)SO(4), the tyrosine-detected folding reaction occurs before proline isomerization and yields a folded intermediate I(N) that is able to bind the specific inhibitor 2′-CMP. The results demonstrate that a folding intermediate is spectrally detectable when folding occurs at low temperatures. They suggest that low temperatures provide suitable conditions for determining the kinetic pathway of folding by characterizing folding intermediates.